The effect of seasonal variation on macromineral contents of sainfoin genotypes and assessments with biplot analysis - Sayar, Mehmet Salih; Han, Yavuz (Progress in Nutrition, 2023)
The use of quality forages in animal nutrition will make great contribution to increase in animal products both in quantity and quality. Macromineral content is an important factor affecting the quality of forages, and the contents in forages can vary due to many factors. Seasonal variation is one of the among the factors, and the study was held to reveal the effect of spring and autumn seasons cuttings on macromineral contents of sainfoin (Onobrychis viciifolia Scop.) which is one of the important and mostly cultivated perennial legume forage species in Turkey. For this reason; a field experiment was conducted according to randomized blocks design with three replications. The study results showed that there were highly significant differences (P